2011
DOI: 10.1088/0964-1726/20/8/085014
|View full text |Cite
|
Sign up to set email alerts
|

Vibration harvesting in traffic tunnels to power wireless sensor nodes

Abstract: Monitoring the traffic and the structural health of traffic tunnels requires numerous sensors. Powering these remote and partially embedded sensors from ambient energies will reduce maintenance costs, and improve the sensor network performance. This work reports on vibration levels detected in railway and road tunnels as a potential energy source for embedded sensors. The measurement results showed that the vibrations at any location in the road tunnel and at the wall in the railway tunnel are too small for us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 21 publications
0
57
0
2
Order By: Relevance
“…Additionally different brass weights have been used to cross correlate the effect of different moments of inertia. The electro motor used in the former study [1] was replaced by a compressed air motor MRD 38-1460 from Mannesmann-Demag (Figure 2 right). This motor was used to circumvent the pickup of magnetic stray fields formerly observed from the experiments with the electro motor.…”
Section: Design Concept and Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally different brass weights have been used to cross correlate the effect of different moments of inertia. The electro motor used in the former study [1] was replaced by a compressed air motor MRD 38-1460 from Mannesmann-Demag (Figure 2 right). This motor was used to circumvent the pickup of magnetic stray fields formerly observed from the experiments with the electro motor.…”
Section: Design Concept and Experimental Setupmentioning
confidence: 99%
“…In previous publications we have shown that a wireless sensor node mounted to a railroad track can be powered by vibrations of a passing train [1]. Applications for this systems lie in the field of structural health monitoring in tunnels, but also other applications are feasible and useful, such as train position or passage detection, or wheel health monitoring of the passing train [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mainly two mechanisms are used to convert this mechanical energy to electrical one which are piezoelectric [1][2][3] and electromagnetic principles [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Comparing to energy harvesting for large-scale alternative energy generation using wind turbines and solar cells is mature technology, the development of energy harvesting technology by using piezoelectric devices on a scale appropriate for small, low-power, embedded wireless sensing systems is still in its developmental stage, particularly for application of structural health monitoring sensing system. 6 Wischke et al 7 have investigated the feasibility of harvesting energy from traffic-induced vibrations in railway and road tunnels to power embedded structure health monitoring sensors. They concluded that the trafficinduced vibrations at any location in the road tunnel and at the wall in the railway tunnel are too small for useful vibration harvesting by using the cantileverbased piezoelectric generator.…”
Section: Introductionmentioning
confidence: 99%